The Recognition of a Foreign Adoption– The Human Rights Principles and Croatian Reality - Drventić Barišin, Martina (Central European Academy Law Review, 2023)
Any person crossing a border wants to have his or her civil status recognised in the host country. Reasons of a personal nature primarily drive such an endeavour. Recognising one’s personal status may also play a significant role in exercising many other rights. When a host state refuses to recognise the personal status or family ties already enjoyed in the territory of another state, this may constitute a breach of the individual’s right to respect for private and family life and be contrary to the standard on the prohibition of discrimination. The difficulties arising in cross-border status recognition mainly stem from the pluralism of national legal systems. The Republic of Croatia has ratified many international documents whose provisions guarantee the right to personal status and has been bound by the EU’s acquis communautaire. The national law, dispersed in several acts, has regulated the mere recognition of personal status acquired abroad. This research starts with an overview of the national legal regulation of cross-border recognition of status in the Republic of Croatia, focusing on recognition of the adoption established abroad. The research puts the national legal framework into the context of the human rights principles derived from the international and EU legal framework.